Effect of Large Meshes on the Body of Trawl Net in Energy Conservation - B.B., Nayak; D.S., Sheshappa (Fishery Technology, 2025)
Incorporation of large meshes in the body of trawl nets reduces the drag substantially and thereby the fuel consumption. Comparative trawling of 28.6 m large mesh four-seam trawl with 26.7 m high opening bottom trawl were conducted off Mangalorc coast during D<.>cember 1989 to May 1990. The large mesh trawl was found to register 33-34% less resistance than the high opening bottom trawl at an average trawling speed of 2-2.5 knots according to theoretical C41lculaUons without any significant effect on catch.